Disturbance Observer-based Formation Tracking Control Of Multiple Quadrotors In The Presence Of Disturbances - Izzuddin M Lazim; Abdul Rashid Husain; Zaharuddin Mohamed; Mohd Ariffanan Mohd Basri; Nurul Adilla Mohd Subha; Liyana Ramli (SAGE Publications, 2024)
Indexed by ERA